Fintech and Start-ups: A Systematic Literature Review - Sanchez Obando, Jhon Wilder; Duque-Méndez, Néstor Darío; Tapasco-Rueda, Andrea Ximena (Universidad Pedagógica y Tecnológica de Colombia, 2023)
Fintech is the application of the technologies of the fourth industrial revolution in the financial field. In recent years, it has aroused growing interest from various financial actors and specialties, thanks to its relevant characteristics such as information security, increased performance, and decentralization. Despite the positive aspects of fintech, there are some trends in its application that require overcoming certain problems such as regulation, technological scalability, and hybridization. Therefore, a systematic overview is considered necessary in which information is collected to provide an overview of the state of the art related to the application of fintech and start-ups to serve as a reference for future research in this field. To this end, a systematic literature review was conducted using the PRISMA protocol in combination with the Tree of Science (ToS) algorithm. Articles published between 2016 and 2021 were found in the Web of Science, Google Scholar, Scopus and IEEE Xplore databases, where the Tree of Science (ToS) algorithm was then applied to identify the most relevant literature on the topic. As a result, 72 articles were analyzed. The analysis of the selected articles provided valuable information and answered the research questions posed in the PRISMA protocol. The results indicate as research trends on the topic: business financing, innovation and financial information, financial technology and finance and regulation. Fintech is a revolutionary innovation that creates opportunities in the market and in the financial world, which is why prototypes are being developed worldwide.